Neuroprotection of Gastrodia elata polyphenols against H2O2-induced PC12 cell cytotoxicity by reducing oxidative stress - Tan, Weijian; Zheng, Qinhua; Feng, Kexin; Feng, Xiaolin; Zhong, Wenting; Liao, Caiyu; Li, Shangjian; Liu, Yuntong; Hu, Wenzhong (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that severely affects the quality of life of patients. Oxidative stress (OS) runs through the pathogenesis of AD with Aβ，Abnormal Tau protein and neuroinflammatory reaction jointly promote the development of AD. The development of plant-based natural antioxidants may provide a new idea for the development of drugs for the prevention and treatment of AD. Gastrodia elata is a well-known homology of medicine and food plant that has been used for centuries in China and other East Asian countries to treat central nervous system disorders. In this study, we focused on the potential of the extract of Gastrodia elata polyphenols (GPP), for the prevention and treatment of AD. H2O2 induced PC12 cell damage was used to simulate the oxidative stress of AD. The effects of GPP on the injury model were evaluated by cell survival rate, lactate dehydrogenase (LDH), lipid peroxidation (MDA), production of intracellular antioxidant enzymes, reactive oxygen species (ROS), mitochondrial membrane potential (MMP), cellular inflammation level and apoptosis level. The results showed that GPP pretreatment had a protective effect by increasing cell viability, reducing LDH infiltration(P < 0.05), decreasing MDA and increasing intracellular antioxidant enzymes (P < 0.05), diminishing ROS production and decreasing MMP(P < 0.05), reducing cell inflammation and decreasing apoptosis (P < 0.05). These results suggest that GPP has good neuroprotective ability which may be used for the prevention or treatment of AD, and providing a reference for the development of functional foods or drugs from Gastrodia elata.